O ritual de fabricação do brinquedo de miriti: um olhar a partir dos relatos de um artesão - SANTOS, Graciete Cardoso dos (2022)
The work “Ritual of the manufacture of the miriti toy” exposes the activities developed in a research carried out during the Educational Anthropology discipline, of the Pedagogy Degree course at the Federal University of Pará (UFPA) - Campus Abaetetuba. Aiming to know how the ritual of manufacturing the miriti toy occurs, in order to put into practice the theories discussed in the classroom. To this end, authors such as Silva (1997) and Laplantine (2003) supported us theoretically during the course of the research. As a methodology, a semi-structured interview directed to a craftsman in the municipality was adopted, where the deep relationship between the artist and his art was perceived, imbued with a feeling that goes beyond the material, reaching the search for social improvements through projects developed by the Craftsman.